Cardiopulmonary exercise testing in systolic heart failure in 2014: the evolving prognostic role. (1st September 2014) - Corrà, Ugo; Piepoli, Massimo F.; Adamopoulos, Stamatis; Agostoni, Piergiuseppe; Coats, Andrew J.S.; Conraads, Viviane; Lambrinou, Ekaterini; Pieske, Burkert; Piotrowicz, Ewa; Schmid, Jean‐Paul; Seferović, Petar M.; Anker, Stefan D.; et al.
<x xml:space="preserve">Abstract</x> The relationship between exercise capacity, as assessed by peak oxygen consumption, and outcome is well established in heart failure (HF), but the predictive value of cardiopulmonary exercise testing (CPET) has been recently questioned, for two main reasons. First, the decisional power of CPET in the selection of heart transplantation candidates has diminished, since newer therapeutic options and the shortage of donor hearts have restricted this curative option to extremely advanced HF patients, frequently not able to perform a symptom‐limited CPET. Secondly, the use of CPET has become more complex and sophisticated, with many promising new prognostic indexes proposed each year. Thus, a modern interpretation of CPET calls for selective expertise that is not routinely available in all HF centres. This position paper examines the history of CPET in risk stratification in HF. Throughout five phases of achievements, the journey from a single CPET parameter (i.e. peak oxygen consumption) to a multiparametric approach embracing the full clinical picture in HF—including functional, neurohumoral, and laboratory findings—is illustrated and discussed. An innovative multifactorial model is proposed, with CPET at its core, that helps optimize our understanding and management of HF patients.